Topological structure and piezoelectric property synergistically controllable oriented polylactic acid nanofiber membrane, preparation method and application thereof

CN119663551BActive Publication Date: 2026-11-03NANTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411843091.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2026-11-03
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

现有聚乳酸纤维表面拓扑结构和压电性质难以实现协同可控,限制其在生物组织工程中的应用。

Method used

Oriented nanofiber membranes were prepared by controlling the treatment time of the fibers with organic reagents using high voltage electrospinning technology. The fiber membranes were then impregnated with ethyl acetate or N,N-dimethylamide solvent for a preset time to regulate their topological structure and piezoelectric properties.

Benefits of technology

The topology and piezoelectric properties were synergistically controllable, improving the piezoelectric properties of polylactic acid fibers. In particular, the piezoelectric properties were significantly enhanced after treatment with N,N-dimethylamide for 20 min, and the effect was best after treatment with ethyl acetate for 10 min.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663551B_ABST
    Figure CN119663551B_ABST
Patent Text Reader

Abstract

The application relates to an oriented polylactic acid nanofiber membrane with a controllable topological structure and piezoelectric property and a preparation method and application thereof, and belongs to the field of biomaterial preparation. First, high-pressure electrostatic spinning technology is used to process polylactic acid with a certain concentration into superfine nanofibers, a drum connected with a ground wire is used to receive the fibers, and highly-oriented polylactic acid nanofibers are collected, then the polylactic acid nanofibers are soaked in ethyl acetate or N,N-dimethylformamide, on one hand, the surface morphology of the oriented polylactic acid fibers is reshaped, and on the other hand, the crystallinity of the polylactic acid membrane is changed to regulate the piezoelectric property of the oriented polylactic acid fibers, research finds that when the N,N-dimethylformamide is treated for 20 min, the piezoelectricity of the polylactic acid fibers is significantly enhanced, and the piezoelectric effect is best when the ethyl acetate is treated for 10 min. The oriented polylactic acid nanofiber membrane provided by the application can be applied to the preparation of degradable medical biomaterials and is used for promoting the regeneration of biological tissues or nerves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomaterial preparation, and specifically relates to an oriented polylactic acid nanofiber membrane with synergistic control over topological structure and piezoelectric properties, its preparation method and application. Background Technology

[0002] Polylactic acid (PLA) is a biodegradable biomedical material recognized by the U.S. Food and Drug Administration (FDA). PLA has advantages such as soft texture, mild processing conditions, and good biocompatibility. Current research has found that PLA can be endowed with piezoelectric effect after special treatment. PLA is mainly used in the form of films and fiber films. Common methods to achieve piezoelectricity include heat stretching, electrospinning, and template impregnation. Among them, electrospinning is a simple method to prepare PLA films. An electric field and a high-speed rotating roller receiver can obtain highly oriented PLA fiber films, so that its dipoles are arranged parallel to the direction of the molecular chain perpendicular to the direction of the molecular chain, thereby generating shear piezoelectricity. This further increases the added value of PLA. The excellent biodegradability and piezoelectricity make PLA more likely to be used in implantable bioelectronics, especially for in vivo therapy and power generation. On the other hand, polylactic acid (PLA) fiber, as a commonly used biodegradable medical material in tissue engineering, provides physical clues for tissue regeneration and functional recovery through its surface topology. However, the controllability of the surface topology and piezoelectricity of PLA fiber remains a challenge. Customizing the topology and piezoelectric output will further promote the application of PLA fiber in bioengineering, such as biodegradable medical biomaterials, to promote the regeneration of biological tissues or nerves. Summary of the Invention

[0003] This invention relates to the preparation of an oriented polylactic acid nanofiber membrane with synergistic control over its topology and piezoelectric properties, as well as its preparation method and application. The topology and piezoelectricity can be controlled by adjusting the treatment time of the fibers with organic reagents.

[0004] A first aspect of the present invention provides a method for preparing an oriented polylactic acid nanofiber membrane with synergistic controllable topology and piezoelectric properties, the method comprising the following steps:

[0005] S1. Add L-polylactic acid and polyethylene oxide to the first solvent to obtain the spinning solution;

[0006] S2. Electrospin the spinning solution to obtain an oriented nanofiber membrane;

[0007] S3. The oriented nanofiber membrane is impregnated with a second solvent for a predetermined time to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and predetermined piezoelectric properties. The second solvent is ethyl acetate or N,N-dimethylamide.

[0008] In some embodiments, the first solvent is trifluoroethanol.

[0009] In some embodiments, in step S1, for every 10 mL of the first solvent, the amount of L-polylactic acid is 0.25 g to 0.45 g, and the amount of polyethylene oxide is 0.05 g to 0.25 g.

[0010] In some embodiments, step S2 specifically involves: electrospinning the spinning solution into an oriented nanofiber membrane using a high-voltage electrospinning device, wherein the spinning solution driving rate of the high-voltage electrospinning device is 0.5 mL / h, the voltage is 7-10 kV, and a roller wrapped with aluminum foil at a rotation speed of 2000 r / min is used to receive the fibers and collect the oriented nanofiber membrane.

[0011] In some embodiments, the preset time in step S3 is 10-30 minutes.

[0012] In some embodiments, in step S3, the preset time is set according to preset piezoelectric performance requirements and the type of the second solvent.

[0013] In some embodiments, the second solvent is ethyl acetate, and the preset time is 10 min.

[0014] In some embodiments, the second solvent is N,N-dimethylamide, and the preset time is 20 min.

[0015] In a second aspect, the present invention provides an oriented polylactic acid nanofiber membrane prepared according to the above-described preparation method.

[0016] A third aspect of the present invention provides the application of the above-described oriented polylactic acid nanofiber membrane in the preparation of biodegradable medical biomaterials, wherein the biodegradable medical biomaterials are used to promote the regeneration of biological tissues or nerves.

[0017] The oriented polylactic acid nanofiber membrane with synergistic controllable topology and piezoelectric properties, its preparation method, and its application, as described in the embodiments of the present invention, have the following advantages:

[0018] First, high-voltage electrospinning technology was employed, using a grounded roller to collect highly oriented ultrafine polylactic acid (PLA) nanofibers. Then, the oriented fiber membrane was impregnated with ethyl acetate or N,N-dimethylamide. Different treatment times reshaped the surface morphology of the oriented PLA fibers. Furthermore, the crystallinity of the PLA membrane also affected the properties, further modulating the piezoelectric properties of the oriented PLA fibers. The study found that N,N-dimethylamide treatment improved the piezoelectric properties of the PLA fibers; when the treatment time was 20 min, the piezoelectricity of the PLA fibers was significantly enhanced, with an output current of 7.58 × 10⁻⁶. -5 ±7.44*10 -6A. Ethyl acetate treatment also enhances the piezoelectric properties of polylactic acid fibers. The best piezoelectric effect is observed when the treatment time is 10 minutes, with an output current of 1.07*10⁻⁶. -9 ±1.05*10 -12 A. In general, the surface topology and piezoelectric properties of polylactic acid fibers can be indirectly controlled by adjusting the impregnation time with ethyl acetate and N,N-dimethylamide. Attached Figure Description

[0019] Figure 1 The images are scanning electron microscope (SEM) images of untreated polylactic acid (PLA) fibers (sample 1) and oriented PLA fibers (samples 2-4) treated with ethyl acetate for 10 min, 20 min, and 30 min, respectively, and the electrical signal output diagrams under 2 N pressure.

[0020] Figure 2 The graph shows the electrical signal output current values ​​of untreated polylactic acid fiber (sample 1) and oriented polylactic acid fiber (samples 2-4) treated with ethyl acetate for 10 min, 20 min, and 30 min under 2N pressure.

[0021] Figure 3 The images are scanning electron microscope (SEM) images of untreated polylactic acid (PLA) fibers (sample 1) and oriented PLA fibers (samples 5-7) treated with N,N-dimethylamide for 10 min, 20 min, and 30 min, respectively, and the electrical signal output images under 2N pressure.

[0022] Figure 4 The graph shows the electrical signal output current values ​​of untreated polylactic acid fiber (sample 1) and oriented polylactic acid fiber (samples 5-7) treated with N,N-dimethylamide for 10 min, 20 min, and 30 min under 2N pressure. Detailed Implementation

[0023] The present invention will be further described below with reference to specific implementation steps. It should be understood that these embodiments are for illustrative purposes only and not for limiting the scope of the invention. Furthermore, it should be understood that after reading the description of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0024] Polylactic acid (Mw 100,000, Jinan Daigang Bioengineering Co., Ltd.)

[0025] Polyethylene oxide (Mr = 5000kDa, AlfaAesar)

[0026] Trifluoroethanol (T819391, McLean)

[0027] Ethyl acetate (E809174, Maclean's)

[0028] N,N-Dimethylamide (D112004, Aladdin)

[0029] Example 1

[0030] At room temperature, 0.45 g of PLLA (polylactic acid) and 0.05 g of PEO (polyethylene oxide, Mr = 5000 kDa) were added to 10 mL of LTFE (trifluoroethanol) and stirred overnight at room temperature to dissolve. The PLLA solution was then electrospun into nanofibers using a high-voltage electrospinning apparatus. The solution propulsion rate was controlled at 0.5 mL / h, and the voltage at 7 kV. A high-speed rotating roller wrapped with aluminum foil was used to receive the fiber membrane at a speed of 2000 r / min. The oriented nanofiber membrane was collected and dried in a vacuum drying oven for 24 h.

[0031] Example 2

[0032] At room temperature, 0.45 g of PLLA (polylactic acid) and 0.05 g of PEO (polyethylene oxide, Mr = 5000 kDa) were added to 10 mL of LTFE (trifluoroethanol) and dissolved overnight at room temperature with stirring. The PLLA solution was then electrospun into nanofibers using a high-voltage electrospinning apparatus. The solution propulsion rate was controlled at 0.5 mL / h, and the voltage was 8 kV. A high-speed rotating roller wrapped with aluminum foil was used to receive the fiber membrane at a speed of 2000 r / min. The oriented fiber membrane was collected and placed in a vacuum drying oven to dry for 24 h.

[0033] The dried membrane was cut into 2cm×2cm films, and the fiber membrane was fixed with stainless steel clips. The oriented fiber membrane was completely immersed in ethyl acetate. After immersion treatment for 10 minutes, the oriented fiber membrane was removed to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and preset piezoelectric properties.

[0034] Example 3

[0035] At room temperature, 0.9 g of PLLA (polylactic acid) and 0.1 g of PEO (polyethylene oxide, Mr = 5000 kDa) were added to 20 mL of LTFE (trifluoroethanol) and dissolved overnight at room temperature with stirring. The PLLA solution was then electrospun into nanofibers using a high-voltage electrospinning apparatus. The solution propulsion rate was controlled at 0.5 mL / h, and the voltage at 7 kV. A high-speed rotating roller wrapped with aluminum foil was used to receive the fiber membrane at a speed of 2000 r / min. The oriented fiber membrane was collected and placed in a vacuum drying oven to dry for 24 h.

[0036] The dried membrane was cut into 2cm×2cm films, and the fiber membrane was fixed with stainless steel clips. The oriented fiber membrane was completely immersed in ethyl acetate. After immersion treatment for 20 minutes, the oriented fiber membrane was removed to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and preset piezoelectric properties.

[0037] Example 4

[0038] At room temperature, 0.9 g of PLLA (polylactic acid) and 0.1 g of PEO (polyethylene oxide, Mr = 5000 kDa) were added to 20 mL of TFE (trifluoroethanol) and stirred overnight at room temperature to dissolve. The polylactic acid solution was electrospun into nanofibers using a high-voltage electrospinning apparatus. The solution propulsion rate was controlled at 0.5 mL / h, and the voltage at 7 kV. A high-speed rotating roller wrapped with aluminum foil was used to receive the fiber membrane at a speed of 2000 r / min. The oriented fiber membrane was collected and placed in a vacuum drying oven to dry for 24 h.

[0039] The dried membrane was cut into 2cm×2cm films, and the fiber membrane was fixed with stainless steel clips. The oriented fiber membrane was completely immersed in ethyl acetate. After immersion treatment for 30 minutes, the oriented fiber membrane was removed to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and preset piezoelectric properties.

[0040] Example 5

[0041] At room temperature, 0.9 g of PLLA (polylactic acid) and 0.1 g of PEO (polyethylene oxide, Mr = 5000 kDa) were added to 20 mL of TFE (trifluoroethanol) and stirred overnight at room temperature to dissolve. The polylactic acid solution was electrospun into nanofibers using a high-voltage electrospinning apparatus. The solution propulsion rate was controlled at 0.5 mL / h, and the voltage at 7 kV. A high-speed rotating roller wrapped with aluminum foil was used to receive the fiber membrane at a speed of 2000 r / min. The oriented fiber membrane was collected and placed in a vacuum drying oven to dry for 24 h.

[0042] The dried membrane was cut into 2cm×2cm films, and the fiber membrane was fixed with stainless steel clips. The oriented fiber membrane was completely immersed in N,N-dimethylamide. After immersion treatment for 10 minutes, the oriented fiber membrane was removed to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and preset piezoelectric properties.

[0043] Example 6

[0044] At room temperature, 0.9 g of PLLA (polylactic acid) and 0.1 g of PEO (polyethylene oxide, Mr = 5000 kDa) were added to 20 mL of TFE (trifluoroethanol) and stirred overnight at room temperature to dissolve. The polylactic acid solution was electrospun into nanofibers using a high-voltage electrospinning apparatus. The solution propulsion rate was controlled at 0.5 mL / h, and the voltage at 7 kV. A high-speed rotating roller wrapped with aluminum foil was used to receive the fiber membrane at a speed of 2000 r / min. The oriented fiber membrane was collected and placed in a vacuum drying oven to dry for 24 h.

[0045] The dried membrane was cut into 2cm×2cm films, and the fiber membrane was fixed with stainless steel clips. The oriented fiber membrane was completely immersed in N,N-dimethylamide. After immersion treatment for 20 minutes, the oriented fiber membrane was removed to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and preset piezoelectric properties.

[0046] Example 7

[0047] At room temperature, 0.9 g of PLLA (polylactic acid) and 0.1 g of PEO (polyethylene oxide, Mr = 5000 kDa) were added to 20 mL of TFE (trifluoroethanol) and stirred overnight at room temperature to dissolve. The polylactic acid solution was electrospun into nanofibers using a high-voltage electrospinning apparatus. The solution propulsion rate was controlled at 0.5 mL / h, and the voltage at 7 kV. A high-speed rotating roller wrapped with aluminum foil was used to receive the fiber membrane at a speed of 2000 r / min. The oriented fiber membrane was collected and placed in a vacuum drying oven to dry for 24 h.

[0048] The dried membrane was cut into 2cm×2cm films, and the fiber membrane was fixed with stainless steel clips. The oriented fiber membrane was completely immersed in N,N-dimethylamide. After immersion treatment for 30 minutes, the oriented fiber membrane was removed to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and preset piezoelectric properties.

[0049] Test case

[0050] The samples from Examples 1-7 were placed between two glass plates connected to two copper electrodes (ensuring that both ends of the film were connected to the two copper electrodes respectively), and a force of 2N was applied using a pressure gauge. The piezoelectricity was then tested using an electrochemical workstation.

[0051] Electron micrographs of samples 1-4 and their electrical signal output under 2N pressure are shown below. Figure 1 As shown. According to Figure 1 It is known that treating the oriented nanofiber membrane with ethyl acetate will further change the surface topology of the oriented nanofiber membrane and improve its piezoelectric properties.

[0052] The output current of the sample in Example 1 (untreated oriented nanofiber membrane) was 1.24*10.-12 ±1.16*10 -13 A.

[0053] The electrical signal output current of the sample in Example 2 (sample treated with ethyl acetate for 10 min) was 1.07*10. -9 ±1.05*10 -12 A. The fiber membrane treated with ethyl acetate for 10 min showed the greatest improvement in piezoelectric properties compared to the fiber membrane not treated with ethyl acetate.

[0054] The electrical signal output current of the sample in Example 3 (sample treated with ethyl acetate for 20 min) was 2.37 * 10⁻⁶. -10 ±6.75*10 -12 A. The piezoelectric properties of the fiber membrane treated with ethyl acetate for 20 min were significantly improved compared to the fiber membrane that was not treated with ethyl acetate.

[0055] The electrical signal output current of the sample in Example 4 (sample treated with ethyl acetate for 30 min) was 1.97*10. -10 ±4.02*10 -12 A. The piezoelectric properties of the fiber membrane treated with ethyl acetate for 30 min were improved compared to those of the untreated fiber membrane.

[0056] The electrical signal output current of the sample in Example 5 (sample treated with N-dimethylamide for 10 min) was 9.31 * 10⁻⁶. -10 ±1.16*10 -11 A. The piezoelectric properties of the fiber membrane treated with N,N-dimethylamide were slightly improved compared to those of the fiber membrane that was not treated with N,N-dimethylamide.

[0057] The electrical signal output current of the sample in Example 6 (sample treated with N-dimethylamide for 20 min) was 7.58*10. -5 ±7.44*10 -6 A. After 20 min, the piezoelectric properties of the fiber membrane treated with N,N-dimethylamide were improved to the optimal level compared to the fiber membrane that was not treated with N,N-dimethylamide.

[0058] The electrical signal output current of the sample in Example 7 (sample treated with N-dimethylamide for 30 min) was 8.57*10. -11 ±1.34*10 -11 A. The piezoelectric properties of the fiber membrane treated with N,N-dimethylamide were improved compared with those of the fiber membrane that was not treated with N,N-dimethylamide.

[0059] The oriented polylactic acid nanofiber membrane with synergistic controllable topology and piezoelectric properties, its preparation method, and its application, as described in the embodiments of the present invention, have at least one of the following advantages:

[0060] The oriented polylactic acid nanofiber membrane with synergistic controllable topology and piezoelectric properties, its preparation method, and its application, as described in the embodiments of the present invention, have the following advantages:

[0061] First, high-voltage electrospinning technology was employed, using a grounded roller to collect highly oriented ultrafine polylactic acid (PLA) nanofibers. Then, the oriented fiber membrane was impregnated with ethyl acetate or N,N-dimethylamide. Different treatment times reshaped the surface morphology of the oriented PLA fibers. Furthermore, the crystallinity of the PLA membrane also affected the properties, further modulating the piezoelectric properties of the oriented PLA fibers. The study found that N,N-dimethylamide treatment improved the piezoelectric properties of the PLA fibers; when the treatment time was 20 min, the piezoelectricity of the PLA fibers was significantly enhanced, with an output current of 7.58 × 10⁻⁶. -5 ±7.44*10 -6 A. Ethyl acetate treatment also enhances the piezoelectric properties of polylactic acid fibers. The best piezoelectric effect is observed when the treatment time is 10 minutes, with an output current of 1.07*10⁻⁶. -9 ±1.05*10 -12 A. In general, the surface topology and piezoelectric properties of polylactic acid fibers can be indirectly controlled by adjusting the impregnation time with ethyl acetate and N,N-dimethylamide.

Claims

1. A method for preparing an oriented polylactic acid nanofiber membrane with synergistic controllable topology and piezoelectric properties, characterized in that, The preparation method includes the following steps: S1. Add L-polylactic acid and polyethylene oxide to the first solvent to obtain the spinning solution; S2. Electrospin the spinning solution to obtain an oriented nanofiber membrane; S3. The oriented nanofiber membrane is impregnated with a second solvent for a predetermined time to obtain an oriented polylactic acid nanofiber membrane with a predetermined topological structure and predetermined piezoelectric properties. The second solvent is ethyl acetate or N,N-dimethylamide. The preset time is set according to the preset piezoelectric performance requirements and the type of the second solvent; The piezoelectric performance requirement is: under a pressure of 2N, the output current range is 1.97*10. -10 A~1.07*10 -9 A, and the lower limit allowable deviation is ± 4.02*10 -12 A, the upper limit allowable deviation is ± 1.05*10 -12 A. When the second solvent is ethyl acetate, the preset time is 10-30 min; The piezoelectric performance requirement is: under a pressure of 2N, the output current is 7.58*10. -5 ± 7.44*10 -6 When A is the second solvent being N,N-dimethylamide, the preset time is 20 min.

2. The preparation method according to claim 1, characterized in that, The first solvent is trifluoroethanol.

3. The preparation method according to claim 1, characterized in that, In step S1, for every 10 mL of the first solvent, the amount of L-polylactic acid is 0.25 g to 0.45 g, and the amount of polyethylene oxide is 0.05 g to 0.25 g.

4. The preparation method according to claim 1, characterized in that, Step S2 specifically involves: using a high-voltage electrospinning device to electrospin the spinning solution into an oriented nanofiber membrane. The high-voltage electrospinning device has a spinning solution driving rate of 0.5 mL / h and a voltage of 7~10 kV. A roller wrapped with aluminum foil at a rotation speed of 2000 r / min is used to receive the fibers and collect the oriented nanofiber membrane.

5. The preparation method according to claim 1, characterized in that, The second solvent is ethyl acetate, and the preset time is 10 min.

6. An oriented polylactic acid nanofiber membrane prepared by the preparation method according to any one of claims 1-5.

7. The application of the oriented polylactic acid nanofiber membrane of claim 6 in the preparation of a biodegradable medical biomaterial, wherein the biodegradable medical biomaterial is used to promote the regeneration of biological tissues or nerves.

Citation Information

Patent Citations

  • Micro-nano topological structure PLLA superfine fiber material as well as preparation method and application thereof

    CN116065256A